Investigation of thermal performance and chemical stability of metal infused salt hydrate phase change material for thermal energy storage - Pandey, Adarsh Kumar; Rajamony, Reji Kumar; Samykano, Mahendran; Buddhi, D.; Tyagi, Vineet Veer (Institute of Physics, 2023)
Thermal energy storage (TES) is a technique that is considered a very desirable technology with a high potential to overcome the gap between demand and supply. Phase change materials (PCMs) are considered to be a highly favourable thermal energy storage materials. Besides that, PCM has certain drawbacks, such as lower thermal conductivity and higher light transmission; owing to this, the heat transfer rate and energy storage density are less. The performance of the PCMs can be improved by adding highly conductive nanoparticles. In this study, various weight percentages (0.1% - 5.0%) of Copper (II) oxide nanoparticles are dispersed with salt hydrate phase change materials with melting temperature 50 °C and investigated the thermal and chemical properties using Thermogravimetric analyzer, thermal conductivity analyzer, and Fourier transform infrared spectrum. Results shows that the prepared nanocomposites have chemically and thermally stable up to 467 °C. The thermal conductivity was increased by 62.64%, at 3.0 wt% Copper (II) oxide with salt hydrate PCM. The developed nanocomposites have better thermophysical properties than pure salt hydrate, which may be applied for TES applications like solar water heating, photovoltaic thermal systems, and electronic cooling systems.